Cosmic ray exposure and pre‐atmospheric size of the Gebel Kamil iron meteorite. (13th August 2014) - Ott, U.; Merchel, S.; Herrmann, S.; Pavetich, S.; Rugel, G.; Faestermann, T.; Fimiani, L.; Gomez‐Guzman, J. M.; Hain, K.; Korschinek, G.; Ludwig, P.; D'Orazio, M.; et al.
Abstract Cosmogenic He, Ne, and Ar as well as the radionuclides 10Be, 26Al, 36Cl, 41Ca, 53Mn, and 60Fe have been determined on samples from the Gebel Kamil ungrouped Ni‐rich iron meteorite by noble gas mass spectrometry and accelerator mass spectrometry (AMS), respectively. The meteorite is associated with the Kamil crater in southern Egypt, which is about 45 m in diameter. Samples originate from an individual large fragment ("Individual") as well as from shrapnel. Concentrations of all cosmogenic nuclides—stable and radioactive—are lower by a factor 3–4 in the shrapnel samples than in the Individual. Assuming negligible 36Cl decay during terrestrial residence (indicated by the young crater age <5000 years; Folco et al. 2011), data are consistent with a simple exposure history and a 36Cl‐36Ar cosmic ray exposure age (CRE) of approximately (366 ± 18) Ma (systematic errors not included). Both noble gases and radionuclides point to a pre‐atmospheric radius >85 cm, i.e., a pre‐atmospheric mass >20 tons, with a preferred radius of 115–120 cm (50–60 tons). The analyzed samples came from a depth of approximately 20 cm (Individual) and approximately 50–80 cm (shrapnel). The size of the Gebel Kamil meteoroid determined in this work is close to estimates based on impact cratering models combined with expectations for ablation during passage through the atmosphere (Folco et al. 2010, 2011).